2015
DOI: 10.4236/ajps.2015.619318
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Salt Tolerance Potential of Watermelon (<i>Citrullus lanatus</i>) by Exogenous Application of Salicylic Acid

Abstract: Salicylic acid (SA) is a vital plant growth regulator providing promising role in plant development and adopts defense mechanism to abiotic stresses. Salinity is the most limiting abiotic factor for plant development and growth changes in watermelon by producing reactive oxygen species and ultimately oxidative stress. The present study was aimed to investigate the mechanism involved in salt stress alleviation in watermelon (Citrullus lanatus Thanb. Mavs.) through the foliar application of salicylic acid. Water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Regarding the leaf number, the highest mean value (8.19 leaves) was obtained at the lowest SA concentration (0.15 mM), with a decrease at 0.5 mM and subsequent increase in the higher doses ( Figure 1E). Similar results were found by Ayyub et al (2015), who observed increased leaf number in response to increased salicylic acid concentrations. Regarding the salinity treatment, the highest average was found at the ECw of 1.01 dS m -1 , with 9.25 leaves, decreasing at subsequent salinity levels, with the lowest average (5.50 leaves) obtained at 4.00 dS m -1 , representing a 68.2% decrease ( Figure 1F).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the leaf number, the highest mean value (8.19 leaves) was obtained at the lowest SA concentration (0.15 mM), with a decrease at 0.5 mM and subsequent increase in the higher doses ( Figure 1E). Similar results were found by Ayyub et al (2015), who observed increased leaf number in response to increased salicylic acid concentrations. Regarding the salinity treatment, the highest average was found at the ECw of 1.01 dS m -1 , with 9.25 leaves, decreasing at subsequent salinity levels, with the lowest average (5.50 leaves) obtained at 4.00 dS m -1 , representing a 68.2% decrease ( Figure 1F).…”
Section: Resultssupporting
confidence: 89%
“…Numerous researches have been carried out to attenuate the salinity harmful effects on cultivated species, especially regarding the use of salicylic acid, which is implicated in plant salinity-stress responses (Ayyub et al, 2015;Silva et al, 2018). This acid acts as a regulator of plant development, taking part in several physiological processes, including defense responses to biotic and abiotic stresses (Miura & Tada, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The problem of soil salinization is long-established, dating from well before the evolution of humans and the development of agriculture, but it has been exacerbated by human agricultural practices such as poor irrigation, excessive fertilization, plowing, and climate change [ 1 , 2 , 3 , 4 , 5 ]. The area of saline–alkali land (including various saline and alkaline soils) worldwide is increasing by a rate of about 1 × 10 6 to 1.5 × 10 6 hm 2 per year [ 6 ], already covering over 900 million hectares [ 7 , 8 ] or approximately 10% of the total global land area. It is estimated that by 2050, more than 50% of arable land will face salinization problems [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dessert watermelon is known to have a very low tolerance to salt; thus, research has shown that salt tolerance in watermelon can be improved by application of foliar treatment using 24-epibrassinolide (Cheng et al, 2015). Also, foliar applications using 5mmol/L of salicylic acid was found to be very effective in alleviation of salinity (Ayyub et al, 2015). Using salt tolerant rootstock could represent a viable solution to the problem.…”
Section: Watermelon and Resistance To Abiotic Factorsmentioning
confidence: 99%